Maximizing proof-of-work decentralization - Çulha, Davut (Ingeniería Solidaria, 2024)
Introduction: Blockchain technology is one of the emerging technologies that implements the concept of decentralization. The first application of this technology was with Bitcoin, which is a decentralized application. However, the decentralization of Bitcoin has become problematic due to the formation of mining pools. In this work, decentralization is intended to be maximized. Problem: Decentralization is the main concept of blockchain technologies. However, decentralization suffers mainly from mining pools in the Bitcoin network. Objective: In this work, the proposed solution to maximize upon the decentralized nature of Bitcoin is to revise the consensus protocol of Bitcoin. The proposed novel consensus protocol called Signature Proof-of-Work uses signatures instead of hashes. The proposed method aims to minimize the number of mining pools and maximize the number of solo miners by arguing that no one can share their private keys with others, which would ensure greater decentralization of the network.Methodology: The consensus algorithm in Bitcoin is Proof-of-Work. Proof-of-Work allows for the formation of mining pools. Mining pools control the Bitcoin network and reduce decentralization. Therefore, a novel Proof-of-Work consensus algorithm is proposed to empower decentralization. Results: The proposed consensus algorithm called Signature Proof-of-Work uses signatures instead of hashes. The proposed method aims to minimize the number of mining pools and maximize the number of solo miners by arguing that no one can share their private keys with others, which would ensure greater decentralization of the network. Conclusion: The proposed consensus algorithm minimizes mining pools by enforcing non-shareable private keys. Originality: The proposed consensus algorithm is an enhancement of the default Proof-of-Work algorithm of Bitcoin. The proposed algorithm uses signatures instead of hashes, which differentiates it from the default algorithm. Limitations: In the proposed algorithm, the main argument is that no one shares their private keys. In other words, miners cannot share their private keys with others. If they share their private keys, others can control their own money. Therefore, each miner does not want to collaborate with other miners to mine new blocks. As a result, the mining pools will not be formed.
Keywords: proof-of-work; decentralized consensus; decentralization problems; mining pools; decentralized proof-of-work; pool mining